2015
DOI: 10.1002/joc.4557
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends in precipitation and temperature across the Caribbean

Abstract: This study considers long-term precipitation and temperature variability across the Caribbean using two gridded data sets (CRU TS 3.21 and GPCCv5). We look at trends across four different regions (Northern, Eastern, Southern and Western), for three different seasons (May to July, August to October and November to April) and for three different periods (1901–2012, 1951–2012 and 1979–2012). There are no century-long trends in precipitation in either data set, although all regions (with the exception of the North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 45 publications
4
42
0
1
Order By: Relevance
“…Although we observe trends in several MSD and daily rainfall indices, it would be difficult to unambiguously attribute these tendencies to either natural variability or anthropogenic climate change. Substantial natural decadal variability in Central American rainfall (Hastenrath and Polzin 2012, Anchukaitis et al 2015, Jones et al 2016 makes it a challenge to distinguish the cause of trends over the limited 38 year period of CHIRPS alone. Rising temperatures are known to increase the severity and extent of drought in some regions (Griffin and Anchukaitis 2014, Herrera et al 2018), which could further exacerbate soil moisture deficits during normal MSD conditions and enhance the negative effects of a longer and more irregular MSD, particularly in the Dry Corridor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we observe trends in several MSD and daily rainfall indices, it would be difficult to unambiguously attribute these tendencies to either natural variability or anthropogenic climate change. Substantial natural decadal variability in Central American rainfall (Hastenrath and Polzin 2012, Anchukaitis et al 2015, Jones et al 2016 makes it a challenge to distinguish the cause of trends over the limited 38 year period of CHIRPS alone. Rising temperatures are known to increase the severity and extent of drought in some regions (Griffin and Anchukaitis 2014, Herrera et al 2018), which could further exacerbate soil moisture deficits during normal MSD conditions and enhance the negative effects of a longer and more irregular MSD, particularly in the Dry Corridor.…”
Section: Resultsmentioning
confidence: 99%
“…Despite local reports of changes in rainfall, regional analyzes of instrumental meteorological station data and paleoclimate reconstructions for Central America and the Caribbean do not reveal significant, broad-scale trends in annual or seasonal precipitation totals (Aguilar et al 2005, Anchukaitis et al 2015, Jones et al 2016, Pons et al 2016, Hidalgo et al 2017. One possible origin of this discrepancy is that most anecdotal reports refer to lengthening dry periods and rainfall extremes (Hellin et al 2017, Rice 2018, de Sousa et al 2018, rather than annual or seasonal precipitation totals (Aguilar et al 2005, Neelin et al 2006, Hidalgo et al 2017.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The basic climatology of the region has been described in detail by Taylor and Alfaro (). Many studies discuss the regional climatology in the context of the hurricanes that periodically cross the region during the June to November season (see the recent paper by Jones et al , ). Despite the hurricane season, many studies separate the year into three seasons: May to July, August to October and November to April, although the seasonal breakdown varies across the large region.…”
Section: The Caribbean Region and Available Datamentioning
confidence: 99%
“…Among the climatic changes already seen in the Caribbean has been an increase in surface temperatures. Jones et al (2015) reported statistically significant warming everywhere in the Caribbean for the periods and for over half the region during 1979-2012. Stephenson et al (2014) showed statistically significant warming between 1961-2010 and 1986-2010 using regional station data.…”
Section: Introductionmentioning
confidence: 99%